2022
DOI: 10.1096/fj.202200346r
|View full text |Cite
|
Sign up to set email alerts
|

A new preclinical model of western diet‐induced progression of non‐alcoholic steatohepatitis to hepatocellular carcinoma

Abstract: Non‐alcoholic steatohepatitis (NASH) results from the accumulation of excessive liver lipids leading to hepatocellular injury, inflammation, and fibrosis that greatly increase the risk for hepatocellular carcinoma (HCC). Despite the well‐characterized clinical and histological pathology for NASH‐driven HCC in humans, its etiology remains unclear and there is a deficiency in pre‐clinical models that recapitulate the progression of the human disease. Therefore, we developed a new mouse model amenable to genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…In a newly developed preclinical NASH-HCC model with C57/BL6NJ mice, H19 is in the top ten upregulated genes (GSE197884) (Fig. 4c) [31]. We also found that H19 was significantly upregulated in the liver of HuR hKO mice fed with WDSW for 4 weeks (Fig.…”
Section: Hur Is a Suppressor Of Lncrna H19 Transcriptionmentioning
confidence: 54%
“…In a newly developed preclinical NASH-HCC model with C57/BL6NJ mice, H19 is in the top ten upregulated genes (GSE197884) (Fig. 4c) [31]. We also found that H19 was significantly upregulated in the liver of HuR hKO mice fed with WDSW for 4 weeks (Fig.…”
Section: Hur Is a Suppressor Of Lncrna H19 Transcriptionmentioning
confidence: 54%
“…In a newly developed preclinical NASH–HCC model with C57/BL6NJ mice, H19 is in the top ten upregulated genes (GSE197884) (Fig. 4 c) [ 32 ]. We also found that H19 was significantly upregulated in the liver of HuR hKO mice fed with WDSW for 4 weeks (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, most experimental mice strains fed this type of diet rarely progress to severe forms of NASH or develop HCC, unless there is a genetic predisposition (Takahashi et al, 2012;Nakagawa et al, 2014). Green et al (2022) found the addition of high glucose and fructose water to HFD promoted spontaneous induction of NASH driven HCC after 54 weeks. Similarly, diet high in saturated fat, cholesterol and sucrose promote weight gain, insulin resistance, liver injury and inflammation that is comparable to the human disease phenotype (Machado et al, 2015).…”
Section: Preclinical Models To Study Non-alcoholic Fatty Liver Diseas...mentioning
confidence: 99%